2018
DOI: 10.1001/jama.2018.16069
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Unhealthy Alcohol Use

Abstract: Etherton-Beer CD. The feasibility and effect of deprescribing in older adults on mortality and health: a systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…§ § Estimate not available because relative standard error >0.30. ¶ ¶ Poverty categories are based on the ratio of the respondent's annual household income to the appropriate simplified 2016 federal poverty threshold (given family size: number of adults (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) in the household and number of children (≥0) in the household) defined by the U.S. Census Bureau. This ratio is multiplied by 100 to be expressed as a percentage, and federal poverty thresholds were then used to categorize respondents into four FPL categories: 1) <100% of FPL (poor), 2) ≥100% to <200% of FPL (near poor), 3) ≥200% of FPL (not poor), and 4) unknown.…”
Section: Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…§ § Estimate not available because relative standard error >0.30. ¶ ¶ Poverty categories are based on the ratio of the respondent's annual household income to the appropriate simplified 2016 federal poverty threshold (given family size: number of adults (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) in the household and number of children (≥0) in the household) defined by the U.S. Census Bureau. This ratio is multiplied by 100 to be expressed as a percentage, and federal poverty thresholds were then used to categorize respondents into four FPL categories: 1) <100% of FPL (poor), 2) ≥100% to <200% of FPL (near poor), 3) ≥200% of FPL (not poor), and 4) unknown.…”
Section: Characteristicmentioning
confidence: 99%
“…Binge drinking also increases the risk for adverse health conditions, including some chronic diseases (e.g., breast cancer) and fetal alcohol spectrum disorders (2). In 2004, 2013, and again in 2018, for all U.S. adults aged ≥18 years in primary care, the U.S. Preventive Services Task Force (USPSTF) recommended alcohol screening and brief intervention (alcohol SBI) or counseling for persons whose screening indicated drinking in excess of recommended limits or in ways that increase risk for poor health outcomes (3)(4)(5). However, previous CDC surveillance data indicate that patients report rarely talking to their provider about alcohol use, † and alcohol SBI is traditionally delivered through conversation.…”
mentioning
confidence: 99%
“…Not all adolescents who engage in substance use and associated risk behaviours need highly formalised and intensive treatment. BIs following screening procedures are promising approaches for addressing substance use and associated risks that aim to increase motivation to change behaviour for adolescents who do not meet diagnostic criteria for a substance use disorder (Carney, Myers, Louw, & Okwundu, 2016) but more evidence is needed with this population (Bazzi & Saitz, 2018) to ensure the efficacy of such interventions. Previous studies have found that incorporating a caregiver (e.g., parent) component within BIs have led to significantly better substance use and other behavioural outcomes for adolescents compared to BIs that focus on the adolescent only (Piehler & Winters, 2015;Winters, Lee, Botzet, Fahnhorst, & Nicholson, 2014).…”
mentioning
confidence: 99%
“…Despite the evidence in support of BIs for adolescent substance use (Bazzi & Saitz, 2018), these interventions have rarely been tested in low‐ and middle‐income countries such as South Africa. It is unclear whether interventions developed in other settings will be feasible to conduct in these settings and acceptable to potential service users.…”
mentioning
confidence: 99%
“…10 In contrast to its recommendation for adult patients, the USPSTF did not find sufficient evidence to recommend UAU screening or brief behavioral counseling interventions for adolescents. 11 However, the American Academy of Pediatrics still recommends screening youth for UAU, making routine alcohol screening a reasonable practice for adolescents among most family practice providers. 12 Although many screening tools for AUD are available, the USPSTF determined the Alcohol Use Disorders Identification Test e Concise (AUDIT-C) or Single Alcohol Screening Questionnaire (3-and 1-item screening tools, respectively), have the greatest accuracy for assessing UAU in adults 18 years of age and older.…”
Section: Screening Recommendationsmentioning
confidence: 99%